2020
DOI: 10.12688/gatesopenres.13112.2
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and uptake of the lateral flow urine LAM test in countries with high tuberculosis and HIV/AIDS burden: current landscape and barriers

Abstract: Background: Since 2015, the World Health Organization (WHO) has recommended a commercially available lateral-flow urine LAM test (Alere-LAM) to assist in the diagnosis of tuberculosis (TB) in severely ill people living with HIV (PLHIV). The test can rapidly detect TB in severely ill PLHIV and can identify PLHIV most at-risk of death, leading to mortality reductions. However, its uptake in countries with high burdens of TB and HIV has been slow. To assess the current use landscape and identify barriers to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 20 publications
2
33
2
Order By: Relevance
“…A 2018 study showed that despite high diagnostic accuracy and quick time to results, the ratio of smear microscopy tests to Xpert tests performed in 17 high TB burden countries was six to one (11). A similar trend of low uptake of new TB tests has also been reported for urine lipoarabinomannan (LAM) testing (12).…”
Section: State Of the Artsupporting
confidence: 71%
“…A 2018 study showed that despite high diagnostic accuracy and quick time to results, the ratio of smear microscopy tests to Xpert tests performed in 17 high TB burden countries was six to one (11). A similar trend of low uptake of new TB tests has also been reported for urine lipoarabinomannan (LAM) testing (12).…”
Section: State Of the Artsupporting
confidence: 71%
“…In 2019, over 5 years after the establishment of the WHO policy on LF-LAM, a survey of 31 countries with high TB/HIV burden, with responses obtained from 24, showed that only 11 countries had LF-LAM policies in place, with only 5 countries currently using LF-LAM [10]. Limited budgets, lack of country-specific data, administrative hurdles such as local regulatory approval, lack of coordination between national TB and HIV programs, and small perceived patient population size were the most commonly cited constraints on LF-LAM adoption [10]. There is real potential for a broader and simpler WHO recommendation for SILVAMP-LAM given its higher sensitivity, and this could help to overcome some of these implementation barriers.…”
Section: Plos Medicinementioning
confidence: 99%
“…The commercially available Alere Determine TB LAM lateral flow assay (LF-LAM; Abbott, Chicago, US; in previous studies also called AlereLAM) is a rapid, inexpensive POC TB test [7]. While its use is associated with a mortality benefit in severely ill and immunocompromised PLHIV [2,3], it has only moderate sensitivity in patients with a low CD4 count and has had low programmatic uptake [8][9][10]. We have already reported on the novel Fujifilm SILVAMP TB LAM (SILVAMP-LAM; Fujifilm, Tokyo, Japan; in previous studies also called FujiLAM) assay.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this WHO recommendation, a recent study found that uptake of AlereLAM was limited to only 21% of high-burden TB countries. Respondents cited budget constraints, limited countryspecific data, administrative barriers, insufficient coordination between TB and HIV programs, and perceived small eligible population as primary limitations (14). The recommendation to use urine LAM assays only in patients with HIV substantially limits the test's utility, as HIV-negative patients with pulmonary TB account for over 90% of the global TB burden (15).…”
Section: Rapid Tests For Pulmonary Tbmentioning
confidence: 99%